The seasonal cycle of nitrogen uptake and nitrification in the Atlantic sector of the Southern Ocean - Mdutyana, Mhlangabezi; Thomalla, Sandy; Philibert, Raisaa; Ward, Bess; Fawcett, Sarah (Zenodo, 2020)
This data set shows winter and summer nitrogen (nitrate and ammonium) uptake, net primary production, and nitrification (ammonium and nitrite oxidation) rates from the upper 200 m of the Atlantic sector of the Southern Ocean.